Tgfbi Deficiency Leads to a Reduction in Skeletal Size and Degradation of the Bone Matrix - Lee, Jung-Mi; Lee, Eun-Hye; Kim, In-San; Kim, Jung-Eun (SPRINGER, 2015)
Transforming growth factor-beta-induced gene product-h3 (TGFBI/BIGH3) is an extracellular matrix protein expressed in a wide variety of tissues. TGFBI binds to type I, II, and IV collagens, as well as to biglycan and decorin and plays important roles in cell-to-cell, cell-to-collagen, and cell-to-matrix interactions. Furthermore, TGFBI is involved in cell growth and migration, tumorigenesis, wound healing, and apoptosis. To investigate whether TGFBI is involved in the maintenance of skeletal tissues, Tgfbi knockout mice were generated by crossing male and female Tgfbi heterozygous mice. Skeletal preparation showed that the skeletal size in Tgfbi knockout mice was smaller than in wild-type and heterozygous mice. However, chondrocytic cell alignment in the growth plates, bone mineral density, and bone forming rates were similar in Tgfbi knockout, wild-type, and heterozygous mice. Alterations in skeletal tissue arrangements in Tgfbi knockout mice were estimated from safranin O staining, trichrome staining, and immunohistochemistry for type II and X collagen, and matrix metalloproteinase 13 (MMP13). Cartilage matrix degradation was observed in the articular cartilage of Tgfbi knockout mice. Although the detection of type II collagen in the articular cartilage was lower in Tgfbi knockout mice than wild-type mice, the detection of MMP13 was markedly higher, indicating that Tgfbi deficiency is associated with the degradation of cartilage matrix. These results suggest that TGFBI plays an important role in maintaining skeletal tissues and the cartilage matrix in mice.
Keywords: GROWTH-FACTOR-BETA; ARTICULAR-CARTILAGE; IN-VITRO; CHONDROCYTE DIFFERENTIATION; ENDOCHONDRAL OSSIFICATION; EXTRACELLULAR-MATRIX; BETA-IG-H3 INTERACTS; INDUCED GENE; COLLAGEN-VI; PROTEIN